Uji Efek Ekstrak Etanol Daun Sirsak (Annona muricata L.) terhadap Aterosklerosis Arteri Koroner Burung Puyuh Jantan - Zet Rizal; Surya Dharma; Rusmayanti Rusmayanti (Jurnal Farmasi Higea, 2015)
Has been research about influence of ethanol extract of leaves of soursop (Annona muricata L.) on the formation of coronary artery atherosclerosis of male quail induced  high fat feeding and propylthiourasil. Male quail were divided into five groups , each group getting treatment. Negative controls given standard diet, a positive control was given high fat feeding and propylthiouracil, doses of 50, 100, 200 mg / kg BW ethanol extract administered orally soursop leaves. The treatment is done for 60 day, then take heart, be making preparations histopathology and staining haematoxyllin-eosin. The results showed that the ethanol extract of leaves of soursop dose  50 mg / kg BW selective in preventing atherosclerosis in male quail, when compared with the positive control ( P < 0.05 ). While the administration at a dose of 100 and 200 mg / kg showed no selective in preventing atherosclerosis in male quail, when compared with the positive control .